Influence of Immune Engines in Iraqi Patients with Acute Myeloid Leukemia - Muhammed A.H. Aldabagh (Journal of Global Pharma Technology, 2018)
Acute myeloid leukemia (AML) is heterogeneous disorders originated from the abnormalities in the proliferation and maturation of myeloid progenitors in bone morrow. There is a clinical correlation between immunity engines and disease progression, but this relationship is not completely clear yet. This study was designed to assess the full immune response in Iraqi patients diagnosed with AML. Patients and healthy volunteers were divided into three groups: newly diagnosed untreated, under chemotherapy treatment patients and control group. A significant reduction were seen in C4 and IFN-γ levels in both untreated and treated groups with no significant difference between untreated and treated groups. On the other hand, IL-2 and IL-8 levels increased in untreated and treated groups, whereas IL-4 elevated only in untreated group. Additionally, IL-1α levels were decreased in treated group. Moreover, no differences in IL-10 and GM-CSF levels were found between studied groups. Levels of IGG significantly elevated after treatment. However, no differences in IGA and IGM levels were found. In conclusion, immune engines may have substantial effects on the development of AML disease, and chemotherapy may negatively or positively affect the levels of immune components.Keywords: Acute myeloid leukemia, innate and adaptive immune engines, IL-8, INF-γ, IgG.